Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga, dan Lingkungan Fisik terhadap Kepuasan Pelanggan pada Bakoel Koffie Cikini - Holylur Rachman Atrya; Nurdin Hidayat; Sefrimel Angriani ZN (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the direct influence of product quality, service quality, price, and physical environment on customer satisfaction at Bakoel Koffie Cikini. A quantitative approach with a survey method was employed. Data were collected through online and offline questionnaires distributed to 170 customers of Bakoel Koffie Cikini. The sampling technique used non-probability sampling with purposive sampling, utilizing a 6-point even Likert scale to eliminate neutral response bias. Data were analyzed using multiple linear regression with SPSS. The results of direct effect hypothesis testing show that product quality (β = 0.374; t-value = 5.547; p-value = 0.000) and physical environment (β = 0.319; t-value = 4.745; p-value = 0.000) have a positive and significant influence on customer satisfaction. Conversely, service quality (β = 0.118; t-value = 1.747; p-value = 0.083) and price (β = 0.034; t-value = 0.504; p-value = 0.615) are proven to have no significant influence on customer satisfaction. The four independent variables simultaneously explain 26.0% of the variation in customer satisfaction (R² = 0.260; Adjusted R² = 0.242), while the remainder is explained by other factors outside the model. The practical implication of this study emphasizes that satisfaction enhancement strategies at heritage-themed coffee shops like Bakoel Koffie are no longer effective if relying solely on pricing policies or service quality improvements. Management is advised to prioritize product quality consistency and heritage physical environment maintenance as core strategic focuses.  i